EKSISTENSI SENI PATUNG ARBY SAMAH DARI REALIS KE ABSTRAK - Harissman Harissman; Elvis Elvis; Nia Daniati; Yoan Fahira (Institute of Indonesia Arts and Culture (ISBI) Bandung, 2018)
ABSTRACT The study was intended to comprehend the tendency of Arby Samah sculpture artwork from a realist to an abstract form, and to discuss the existence of Arby Samah in sculpture artwork until he decided to settle in his hometown of West Sumatra. This study uses qualitative methods namely observation, interviews and documents. the theory used refers to the opinions of Kartodirdjo, Becker, and Zolberg.Arby Samah continued his education at ASRI Yogyakarta in 1953 majoring in sculpture. In 1957 Arby Samah made a sculpture called abstract sculpture, the form of abstract at that time had not yet appeared so Arby Samah was known as a pioneer of abstract sculpture in Indonesia. After graduating from college Arby decided to work as an employee at the Yogyakarta army museum, and worked as a civil servant in Jakarta and returned to West Sumatra's hometown working at the Ministry of Education and Culture. During his time as a civil servant his career as a sculptor began to disappear so Arby Samah in the eyes of his friends was considered lost in the development of sculpture in Indonesia. Keywords: Arby Samah, Experiment, Career, Sculpture. ABSTRAK Penelitian dimaksudkan untuk memahami kecenderungan Arby Samah berkarya patung dari bentuk realis ke abstrak, serta membahas eksistensi Arby Samah berkarya patung sampai memutuskan menetap di kampung halamannya Sumatera Barat. Penelitian ini menggunakan metode kualitatif yaitu pengamatan, wawancara dan dokumen. teori yang digunakan merujuk kepada pendapat Kartodirdjo, Becker, dan Zolberg.Arby Samah melanjutkan pendidikannya ke ASRI Yogyakarta tahun 1953 mengambil minat seni patung. Pada tahun 1957 Arby Samah membuat bentuk patung yang dinamakan patung abstrak, bentuk abstrak waktu itu belum muncul sehingga Arby Samah dikenal sebagai pelopor patung abstrak di Indonesia. Setelah metamatkan kuliah Arby memutuskan bekerja pegawai di museum angkatan darat Yogyakarta, dan bekerja sebagai PNS P&K Jakarta dan kembali ke kampung halaman Sumatera Barat bekerja di DEPDIKBUD. Selama menjadi pegawai negeri karirnya sebagai pematung mulai hilang sehingga Arby Samah di mata teman-temannya dianggap hilang dalam perkembangan seni patung di Indonesia. Kata Kunci: Arby Samah, Eksperimen, Karir, Seni Patung